Motor control and working memory in adults with neurological injuries: search neuropsychological and electrophysiological evidence of cognitive-motor interaction - Julio Ernesto Pérez-Parra; Francia Restrepo- (Termedia Publishing House, 2024)
Purpose The shared resource theory between motor and cognitive control maintains that the central nervous system shares the same resources to respond to cognitive and motor demands; that is, there are competing demands in cognitive-motor interaction. Methods Through correlations between motor control and working memory in individuals with neurological injuries, this study aims to provide empirical evidence to support the above theory. Motor control was assessed in postural control and Dominant Upper Extremity (DUE) function and activity. Working memory (WM) was assessed via neuropsychological tests and Cognitive Event-related Potentials (ERPs). Fifty-six individuals with neurological injuries between the ages of 19 and 55 years participated. Results The neuropsychological working memory tests applied (Working Memory Index of the Wechsler Adult Intelligence Scale IV, Trail Making Test - part B, and Corsi Block-Tapping Test - backward span sequence) showed significant correlations between DUE functions and activities (ability to grasp, transport and release, and daily life tasks) (rho = [0.27]-[0.47]). Global postural control and WM did not show significant correlations, and nor did dominant upper extremity motor control with P300 wave latency and N200-P300 amplitudes of ERPs, except for grip strength. Conclusions The present results do not provide conclusive empirical evidence of the cognitive-motor interaction, based on the study of relationships between WM and motor control of DUE. However, there are striking correlations between WM and DUE function and activity, especially referring to instrumental activities of daily living. This finding could apply to the rehabilitation of people with neurological injuries and cognitive impairments.